2018
DOI: 10.1111/1751-7915.13322
|View full text |Cite
|
Sign up to set email alerts
|

New tools for high‐throughput expression of fungal secretory proteins in Saccharomyces cerevisiae and Pichia pastoris

Abstract: Summary Heterologous protein expression in yeast, mostly in Saccharomyces cerevisiae and Pichia pastoris, is a well‐established and widely used technique. It typically requires the construction of an expression vector in Escherichia coli containing the foreign gene and its subsequent transformation into yeast. Although simple, this procedure has important limitations for the expression of large numbers of proteins, that is, for the generation of protein libraries. We describe here the development of a novel sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…With the increasing demand for recombinant proteins, and continued discovery of novel medically useful proteins, the improvement of production technology has become a focus of research exploration. Various excellent expression systems based on different hosts have gradually become the primary tools for protein production, including plant [ 1 ], Escherichia coli ( E. coli ) [ 2 ], insect [ 3 ], yeast [ 4 ], and mammals [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing demand for recombinant proteins, and continued discovery of novel medically useful proteins, the improvement of production technology has become a focus of research exploration. Various excellent expression systems based on different hosts have gradually become the primary tools for protein production, including plant [ 1 ], Escherichia coli ( E. coli ) [ 2 ], insect [ 3 ], yeast [ 4 ], and mammals [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, because of inefficient secretion, many recombinant proteins, particularly therapeutic proteins, have poor yields by P. pastoris [ 32 , 33 , 34 ]. Improving secretion levels through medium optimization or engineering strains may be a reasonable and promising strategy to increase the production of heterologous proteins by P. pastoris [ 35 , 36 , 37 ]. Our previous study has reported that NAC can promote HSA-pFSHβ secretion by increasing intracellular GSH pools [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…A novel system was reported for fast and easy expression of recombinant proteins in S. cerevisiae and P. pastoris. In S. cerevisiae, the gene needs only the transformation of yeast cells with an unpurified PCR product carrying the gene to be expressed, and in P. pastoris, it needs only the isolation of the plasmid generated in S. cerevisiae and its transformation into this second yeast, thus making this system suitable for HTP studies (González et al, 2018). A new, stable, autonomously replicating P. pastoris plasmid vector containing the full-length chromosome 2 centromeric DNA sequence was constructed that exhibits high stability for plasmid retention, facilitating genetic manipulation.…”
Section: Yeastmentioning
confidence: 99%